2002
DOI: 10.4161/cbt.78
|View full text |Cite
|
Sign up to set email alerts
|

Variable Sensitivity of Endothelial Cells to Epirubicin in Xenografts of Human Nasopharyngeal Carcinoma CNE-2 Cells

Abstract: Conventional anticancer drugs show non-specific vascular toxicity, and using anticancer drugs as angiogenesis inhibitors was suggested. However, our previous study suggested that vascular endothelial growth factor (VEGF) protected endothelial cells against chemotherapy drugs in vitro. To further test whether the vascular toxicity of anticancer drugs is active in vivo, epirubicin was i.p. injected into nude mice with s.c. xenografts of human nasopharyngeal carcinoma CNE-2 once (one-day schedule) or once a day f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…15 Strikingly, while slowly released low-dose 5-FU from microcapsules was cytotoxic for a prostatic tumor vasculature, it is a bolus injection and single exposure to free EPI that is apparently cytotoxic to the VX2 tumor target. This is an observation that is in line with Zhang et al study 43 and may pave the way for our technique to possibly become a cryo-assisted antivascular chemotherapy. For the Co-CACH technique to be effective at whole tumor ablation, the injectate should have been distributed to the whole ice ball and tumor margin.…”
Section: Discussionsupporting
confidence: 88%
“…15 Strikingly, while slowly released low-dose 5-FU from microcapsules was cytotoxic for a prostatic tumor vasculature, it is a bolus injection and single exposure to free EPI that is apparently cytotoxic to the VX2 tumor target. This is an observation that is in line with Zhang et al study 43 and may pave the way for our technique to possibly become a cryo-assisted antivascular chemotherapy. For the Co-CACH technique to be effective at whole tumor ablation, the injectate should have been distributed to the whole ice ball and tumor margin.…”
Section: Discussionsupporting
confidence: 88%
“…Reductions in tumor RNA integrity by epirubicin/docetaxel chemotherapy may stem from activation of tumor cell RNases [33,34] or from the release of lysosomal RNases upon tumor cell death [33,35]. Since both epirubicin and docetaxel are cytotoxic to endothelial cells of the tumor vasculature [36][37][38], their effects on tumor RNA quality may also be through nutrient/growth factor deprivation, and/or the induction of hypoxia upon destruction of tumor blood vessels. Consistent with the latter view, MCF-7 breast tumor cells cultured in the laboratory of AP for 72 h under hypoxic conditions with 9 nM epirubicin and 6 nM We also observed that mid-treatment dose-dependent reductions in tumor RIN (but not tumor cellularity) were Tumor RIN may be a much more effective biomarker for measurement of drug response or tumor viability than tumor cellularity, since the former changed in proportion to drug dose level and was correlated with pCR earlier in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of KDR has also been shown to correlate with tumor growth, lymph node metastasis, and resistance to chemotherapy in many kinds of tumors (Thakker et al, 1999;Baek et al, 2000). Binding of VEGF to KDR receptor on the surface of endothelial cells facilitates its autophosphorylation of the protein tyrosine kianse domain (Takahashi et al, 1999;Ichikura et al, 2001;Zhang et al, 2002). Activation of KDR by VEGF results in activation of phosphatidyl inositol 3-kinase/AKT, MAPK, and protein kinase C; the ultimate cellular response is DNA synthesis and cell proliferation.…”
mentioning
confidence: 99%
“…Activation of KDR by VEGF results in activation of phosphatidyl inositol 3-kinase/AKT, MAPK, and protein kinase C; the ultimate cellular response is DNA synthesis and cell proliferation. Vascular endothelial growth factor receptors (VEGFRs) are up-regulated on endothelium at sites of active angiogenesis, providing an opportunity for selective therapeutic intervention (Hanahan, 1997;Zhang et al, 2002).…”
mentioning
confidence: 99%